Comparison of the Efficacy and Safety of Levocetirizine versus Bilastine for the Treatment of Chronic Spontaneous Urticaria in the Pediatric Population: An Observer-blinded Randomized Control Trial - Debashree Sahoo; Maitreyee Panda; Ajaya Kumar Jena; Anil Kumar Panda (Indian Journal of Paediatric Dermatology)
Background: Chronic spontaneous urticaria (CSU) refers to urticaria that has no specific cause or trigger, present on most days of the week for 6 weeks or more. The incidence of chronic urticaria in the pediatric age group is between 0.1% and 3%. Levocetirizine and bilastine are nonsedative second-generation antihistamines used to treat urticaria in both adults and children. Objective: The primary objective was to compare the effectiveness of levocetirizine and bilastine in cases of pediatric CSU using Urticaria Activity Score (UAS) and Urticaria Severity Score (USS). The secondary objective was to evaluate and compare the safety and quality of life (QoL) using the Dermatology Life Quality Index (DLQI) score. Materials and Methods: This was a randomized, observer-blinded study where 65 patients (6–16 years) with a history of urticaria >6 weeks were divided into two groups with computer-generated randomization. Thirty-two patients were included in Group A, who received levocetirizine, and 33 patients were included in Group B, who received bilastine. UAS7, USS, and DLQI were recorded at every visit. The primary outcome was measured using UAS and USS and the secondary outcome in the form of patient’s QoL was assessed using the DLQI score. Laboratory parameters were assessed at the first visit and at the end of 3 months. Results: There was a significant difference (P = 0.002) in UAS7, USS, and DLQI between the baseline and last visit scores for each group. There was no significant difference (P = 0.28) in the scores between the two groups. Laboratory parameters like liver enzymes and complete blood count also did not show any significant differences between the two groups. Conclusion: Both levocetirizine and bilastine are equally effective and safe in the treatment of CSU at the end of 3 months. However, bilastine showed a better fall in the DLQI as compared to levocetirizine.